INTERNATIONAL ACTORS AND INSURGENCY IN THE NIGER DELTA REGION, 1999-2010 - Mahakwe, Anyalebechi, Shammah (Journal of Learning on History and Social Sciences, 2025)
Objective: This paper examines the role of international actors in the Nigeria insurgency between 1999 and 2010, focusing on the socio-economic and environmental legacies of their interventions. It aims to assess the success of international diplomatic efforts in addressing the insurgency's contextual causes, particularly environmental destruction and socio-economic disparities. Method: The study applies the World-Ecology framework to link global capitalist flows with local ecological and social disasters. A historical and qualitative research method is used, drawing from secondary sources such as scholarly publications, non-governmental reports, and global news agencies. Results: The findings reveal that multinational corporations, such as Shell, played a significant role in exacerbating environmental degradation in the Niger Delta, contributing to local resentment and insurgency. While non-governmental organizations like Amnesty International highlighted these abuses, their impact was limited due to the absence of binding legal frameworks and the political complexities involved. Novelty: This paper offers a unique perspective by applying the World-Ecology framework to analyze the intersection of global capitalism, environmental destruction, and socio-political unrest in the Niger Delta. It underscores the failure of international interventions to address the root causes of the insurgency and provides recommendations for improving corporate accountability and advancing peacebuilding efforts.